Short-term results of preventive ileostomy closure - Pažusis, Matas; Maželytė, Rūta; Saladžinskas, Žilvinas (Lietuvos chirurgija, 2018)
[full article and abstract in Lithuanian; abstract in English] Introduction. Preventive ileostomy is most often performed to prevent leakage through low rectal anastomosis. This procedure is most commonly performed during surgery of low rectal cancer. The aim. To review short-term results of preventive ileostomy closure. Method. Retrospective analysis of data about patients operated for ileostomy closure at Coloproctology Section of the Surgery Department of the Lithuanian University of Health Sciences Kaunas Clinics between 2015 and 2017 was carried out. Age, characteristics of complications, number of days of hospitalization, application of neoadjuvant treatment before surgery, time span until ileostomy closure surgery, resection type, type of anastomosis, duration of surgery and postoperative period were analysed. Statistical data analysis was performed using Microsoft Excel software. Results. The data of 64 patients were analysed: 34 men (53.12%) and 30 women (46.87%). These patients underwent surgery for rectal, sigmoid tumours and also for perforated diverticulitis. Patients’ mean age 64±3.1 years. Neoadjuvant treatment before surgery was applied to 16 patients (25%). For all patients, anastomotic leak test was performed before their preventive ileostomy closure surgery. Preventive ileostomy closure surgery took place on average after 5.17±0.95 months. Mean duration of hospitalization was 5.7±0.74 days. Mean duration of the surgery was 75.93±8.57 min. During surgery, segment resection was performed on 38 patients (59.37%). The following anastomoses were formed: “end-to-end” – 20 (52.63%), “end-to-side” – 13 (34.21%) and “side-to-side” – 5 (13.16%). After preventive ileostomy closure surgery early complications affected 7 patients (10.94%). Haemorrhage from anastomosis site was present in 2 (3.12%) patients. For one of them “end-to-side” anastomosis was performed. Another patient underwent marginal resection surgery. Arrhythmia occurred in 2 patients (3.12%). 2 patients (3.12%) developed symptoms of ileus. One of them underwent marginal resection, whereas the other one had “end-to-end” anastomosis. After marginal resection, abdominal wall abscess formed in 1 patient (1.58%). There was no re-operations. Conclusions 1. Most often, during preventive ileostomy closure surgery segment resection is performed. 2. Mean time before ileostomy closure was 5 months. 3. Complications in the postoperative period were more frequent after segment resection. 4. End-to-end anastomosis is associated with few complications during the postoperative period.